PENGGUNAAN MODEL PEMBELAJARAN CORE (CONNECTING ORGANIZING REFLECTING EXTENDING) UNTUK MENINGKATKAN AKTIFITAS SISWA KELAS IV MIN 11 PIDIE PADA MATERI PEDULI TERHADAP MAKHLUK HIDUP - Nasri Diana (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to find out how to increase student activity in the matter of caring for living things, after students learn through the CORE (Connecting Organizing Reflecting Extending) learning model for fourth grade students at MIN 11 Pidie. The research method used is CAR (Classroom Action Research). The subjects in this study were 25 people consisting of 13 male students and 12 female students. Data was collected through observation sheets through teacher activity observation sheets (LOAG), student activity observation sheets (LOAS) and through tests by distributing worksheets to students. This research was conducted in 3 cycles. In the first cycle the average value obtained by students was 56.8 while the classical completeness score obtained was 16%. In cycle II the average value is 68.4, while the classical completeness value obtained is 52%. In the third cycle, the average value obtained increased to 81.8 with a classical completeness score of 92%. So it can be said that there is an increase in student activity in the matter of caring for living things by using the CORE (Connecting Organizing Reflecting Extending) learning model for fourth grade students of MIN 11 Pidie.